Tachydromia fuscinervis Holarctic - Shamshev, Igor V.; Grootaert, Patrick (Zenodo, 2024)
Tachydromia fuscinervis (Frey) (Fig. 7) Tachista fuscinervis Frey, 1915: 3 and 15 (♀). Type locality: Russia, Yakutia, Kharaulakhskiy Ridge near mouth of the Lena River [~ 71°44′N 128°16′E]. Tachydromia fuscinervis : Chvála, 1970: 430 (♀); Shamshev, 1994a: 33, fig. 1 (♂; type material). Material examined: NORTH AMERICA. CANADA . British Columbia: Summit Lake, mi 392 Alaska Hwy., 4500’, 1.vii.1959, R. E. Leech (1 ♀, CNC); same locality, 4500’, 2–4.vii.1959, R. E. Leech (2 ♂, 11 ♀, CNC); same locality, 5000’, 6.vii.1959, R. E. Leech (4 ♀, CNC); same locality, 5000’, 6.vii.1959, E.E. MacDougall (1 ♂, 3 ♀, CNC); same locality, 4500’, 8.vii.1959, R. E. Leech (1 ♀, CNC); same locality, 4500’, 8.vii.1959, E.E. MacDougall (2 ♀, CNC); same locality, 4500’, 11–14.vii.1959, E.E. MacDougall (2 ♀, CNC); same locality, 4500’, 17–19.vii.1959, R. E. Leech (11 ♀, CNC); same locality, 4200’, 21.vii.1959, R. E. Leech (4 ♀, CNC); same locality, 4500’, 23–24.vi.1959, E.E. MacDougall (1 ♂, 1 ♀, CNC). Manitoba: Churchill, 12.vii.1952, J.G. Chillcott (1 ♂, 2 ♀, CNC); Warkworth Cr., nr. Churchill, 21.vi.1952, J.G. Chillcott (1 ♀, CNC); same locality, 7.vii.1952, J.G. Chillcott (1 ♀, CNC); Fort Churchill, 26.vi.1952, J.G. Chillcott (1 ♂, 1 ♀, CNC); Farnsworth L., nr. Churchill, 26.vi.1952, J.G. Chillcott (1 ♀, CNC); same locality, 22.vii.1952, J.G. Chillcott (1 ♀, CNC); Mile 504, Hudson Bay Ry., 21.vi.1952, J.G. Chillcott (1 ♀, CNC); Mile 505, Hudson Bay Ry., 7.vii.1952, J.G. Chillcott (1 ♀, CNC); same locality, 16.vii.1952, J.G. Chillcott (1 ♀, CNC). Yukon: North Fork Crossing, mi. 43 Peel Plt. Rd., 3500’, 24.vi.1962, R. E. Leech (2 ♀, CNC); North Fork Crossing, mi. 42 Peel Plt. Rd., 3500’, 25.vi.1962, R. E. Leech (1 ♂, 2 ♀, CNC); same locality, 26.vi.1962, P.J. Skitsko (1 ♂, 4 ♀, CNC); same locality, on Salix , 26.vi.1962, R. E. Leech (2 ♂, 4 ♀, CNC); North Fork Crossing, mi. 43 Peel Plt. Rd., 3500’, on Salix , 26.vi.1962, R. E. Leech (1 ♀, CNC); North Fork Crossing, Ogilvie Mts. 3.vii.1962, P.J. Skitsko (1 ♀, CNC); same locality, ...